Penelusuran Sumber Definisi Syāẓ Al-Syāfi’ī: Sebuah Kajian Bibliografis - Reza Pahlevi Dalimunthe; Dedi Masri (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2018)
One of the rules of the validity of the Prophet's traditions is to avoid shāẓ. The definition of shāẓ according to al-Shafi'ī (150-204 H) is a single narrator whose history of hadith contradicts with many other narrators. The majority of hadith scholars such as Ibn al-Ṣalāh (577-643 H), chose the definition over the others. This article focuses on searching the bibliographic source for the definition of shāẓ al-Shāfi’ī with an intertext approach. The object is the works of al-Shafi'ī in the field of hadith and a variety of hadith science literature which includes the definition of shāẓ. This study shows that hadith experts generally agree with the definition of shāẓ al-Shafi'ī because it is easier to apply than other definitions. However, they did not clearly mention the title of al-Shafi'i's essay which he referred to, causing misunderstanding as if the source of the definition of shāẓ was Ibn al-Ṣalāḥ, not al-Shafi'ī. One of these misconceptions stems from the unclear reference of Ibn al-Ṣalāḥ himself. This study shows that the bibliographic results of al-Shafi'i's works and transmission lines of definitions are found that the definition of al-Shafi is not found in al-Risalah, but is sourced from al-Manafib al-Shafi al-Baihaqī